Designer Shape Anisotropy on Transition‐Metal‐Dichalcogenide Nanosheets. Issue 9 (9th January 2018) - Martella, Christian; Mennucci, Carlo; Lamperti, Alessio; Cappelluti, Emmanuele; de Mongeot, Francesco Buatier; Molle, Alessandro
Abstract: MoS2 and generally speaking, the wide family of transition‐metal dichalcogenides represents a solid nanotechnology platform on which to engineer a wealth of new and outperforming applications involving 2D materials. An even richer flexibility can be gained by extrinsically inducing an in‐plane shape anisotropy of the nanosheets. Here, the synthesis of anisotropic MoS2 nanosheets is proposed as a prototypical example in this respect starting from a highly conformal chemical vapor deposition on prepatterend substrates and aiming at the more general purpose of tailoring anisotropy of 2D nanosheets by design. This is envisioned to be a suitable configuration for strain engineering as far as strain can be spatially redistributed in morphologically different regions. With a similar approach, both the optical and electronic properties of the 2D transition‐metal dichalcogenides can be tailored over macroscopic sample areas in a self‐organized fashion, thus paving the way for new applications in the field of optical metasurfaces, light harvesting, and catalysis. Abstract : A wealth of new and outperforming applications involving 2D materials like MoS2 can be achieved by inducing an in‐plane shape anisotropy via chemical vapor deposition on prepatterned substrates. Tailoring a 2D anisotropy by design may have relevant impact on the local strain engineering as well as on technology applications in the field of optical metasurfaces, light harvesting, and catalysis.